Effect of the 6-benzylaminopurine on the root morphology of Phaseolus vulgaris under field conditions - Gonzales, Gabriel (2025)
Common bean (Phaseolus vulgaris L.) is a legume crop cultivated and consumed extensively around the world due to its superfood composition and its social-economic impact on farmers. Thus, an experiment with a synthetic cytokinin 6-benzylaminopurine (6-BAP) was conducted in order to assess its effect on the morphological root and shoot traits of the Bayo variety. For that, a Random Complete Block Design (RCBD) was used with 6 treatments (T1: 10 ppm BAP + Drench; T2: 10 ppm BAP + Foliar; T3: 20 ppm BAP + Drench; T4: 20 ppm BAP + Foliar; T5: 30 ppm BAP + Drench; T6: 30 ppm BAP + Foliar and T7: control) and four repetitions. The parameters evaluated were plant height, stem diameter, leaf area, specific leaf area, root length, specific root length, specific root area, root tissue density, dry, and fresh weight matter of root and foliage, and the whole plant. Therefore, no significant differences were found for most parameters, indicating that root and shoot development was not impaired by 6-BAP application, whether applied foliarly or by drenching. The only exception was a reduction in root dry weight at 30 ppm under soil drenching. Nevertheless, root soil exploration and overall plant growth remained unaffected under the tested conditions.